Neurocognitive function and CNS integrity in adult survivors of childhood Hodgkin Lymphoma - a commentary on report from Krull and colleagues - Esiashvili, Natia; Khan, Mohammad; Flowers, Christopher (Translational Pediatrics; Vol 2, No 1 (January 06, 2013): Translational Pediatrics, 2013)
Historically, radiotherapy alone and radiotherapy combined with chemotherapy have led to the cure of many pediatric Hodgkin lymphoma patients. Modern series have demonstrated a 5 year overall survival of greater than 90% for early stage patients. Over the many decades it took to achieve these remarkable results, it became evident that long-term survivors are at increased risk for long-term toxicities such as cardiopulmonary and perhaps neurocognitive toxicities as Krull et al. have suggested (1). However, based on the data presented, it is unclear if the difference is caused solely by the use of outdated mantle field radiation doses of ≥30 Gy vs.